Toward Effective Repatriation of -Illegally Acqui ed Assets in Nigeria - Odusote, Abiodun (Unilag Journal of Humanities, 2019)
repatriating looted state assets in foreign jurisdictions. it is the view of this article [hat the forms of proceeding available in Nigeria to recover looted assets are inadequate. The paper discusses successful assets recovery cases and the not so successful cases involving Nigerian corrupt officials. it also discusses the main challenges [0 assets recovery through criminal proceedings and highlights various approaches to assets recovery. The paper recommends that for effective assets recovery, Nigeria must, among others, enact forfeiture and confiscation laws that should be applied through the civil process rather than the traditional criminal justice system. The article proposes some strategies for assets repatriation, but with a caveat that the success of these proposals is contingent on strong political will on the part of the Nigerian government and its ability to constructively engage the requested state.